The Effect of Flipped Learning through Graphic Organizers toward Writing Skill at MAN 2 Gresik - Aini Vitanofa; Khoirul Anwar (Jetlal, 2018)
Writing is a productive skill that the students give their ideas, knowledge, and opinions about something into the text. Many students consider that writing is a complex skill. In addition, the teacher often spends much time to explain the materials, then it makes the students do not have enough time to finish their writing task to solve those problems, the researcher offers learning method of flipped learning to engage the students doing the activities of writing. Based on the previous studies, flipped learning was given the positive effect in language teaching and learning, such as grammatical performance, reading comprehension, students’ achievement and stress. Thus, making different from the previous study, the researcher applied flipped learning which combines with graphic organizers to teach writing skill. This study was to know the significant effect of flipped learning through graphic organizers toward writing skill. The design of this study was quasi experimental design with 11th grade of social students at MAN 2 Gresik as the subject. The researcher took two classes as the sample by cluster random sampling. They were XI.IPS-1 which consisted of 38 students as experimental group and XI.IPS-2 which consisted of 39 as control group. The data was collected by distributing pre-test and post-test, then researcher analyzed it using SPSS 16.0, independent sample t-test. The research finding showed that there was a significant difference between experimental group and control group. It was proven by the result of the sig. (2-tailed) was 0.012. The sig. (2-tailed) was lower than 0.05 (0.012 < 0.05), so the null hypothesis (H0) can be rejected. It means that flipped learning through graphic organizers had significantly affected toward writing skill. Further, it can be concluded that flipped learning through graphic organizers gave the positive effect toward writing skill at MAN 2 Gresik.The researcher suggests for English teacher to apply flipped learning as an active learning approach in language teaching and learning process. For further researchers, it is hoped to apply flipped learning to develop other skills with the different way.